Candidate of Technical Sciences, Associate Professor, Technologies and organizations of the forest complex, Petrozavodsk State University (PSU), 33, Lenina pr., 185910, Petrozavodsk, Republic of Karelia, Russia. - Kalhori, Elham; Monirpour, Nader; Mirzahosseini, Hassan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present study was to investigate the efficacy of cognitive-behavioral training on labor anxiety in pregnant women. The research method was quasi-experimental (pre-test and post-test) with control group. The study population included all pregnant women who were in late second trimester or early third trimester and had anxiety according to Hartmann labor anxiety questionnaire. Among study population referring to health centers in Tehran, 80 subjects were selected by convenient sampling and were randomly assigned into experimental and control groups. Research data were collected by Hartmann Labor Anxiety Inventory. The experimental group received 12 90-minute sessions of cognitive-behavioral training during pregnancy. Data were analyzed by covariance analysis through SPSS software. The results showed that prenatal cognitive-behavioral skills training was effective in decreasing anxiety in pregnant women and encouraging them to vaginal delivery. The mean score of labor anxiety in pregnant women was lower than the control group after the intervention, and the difference was statistically significant (P